2015 AIChE Spring Meeting & 11th Global Congress on Process Safety : 4th Process Safety Management Mentoring (PSM2) Forum (Center for Chemical Process Safety/AIChE, 2015)
PSM2 is dedicated to sharing all aspects of Process Safety Management in the oil, gas, chemical and allied industries with the next generation of professionals. PSM2 complements the objectives of the other three established symposia in AIChE's Global Congress on Process Safety by focusing on the young practitioners and those new to the world of Process Safety, and by providing a forum where experienced professionals can share their experiences, discuss the role of mentors and mentoring as part of process safety management and career development, and help establish development strategies for academia, industry, and the individuals involved in Process Safety. PSM2 is a forum where Process Safety professionals at all levels can share their experiences and knowledge to help assure continuity of the profession and the safety of our plants. PSM2 is accepting papers dealing with the fundamentals of the various aspects process safety management and mentoring practices and experiences. --